Dalit's inheritance in Hindu religion - Singh, Mahendra (Delhi, 2006)
This book is about the great contribution made by the so-called low castes, presently called Dalits, to the Hindu Religion in spiritual, social and political fields in all period of Indian history. In the chapter 'Aryan Gods Versus Caste' the author has brought out in detail as to how Lord Rama, Krishna and Shiva laid the ideals of liberal society free from rigidity of castes and other man-made distinctions, the teachings of Lord Krishna having the basis of caste as one's guna and karma. The author traces the present rigid structure of Hindu Caste to the period of Manusmriti and other Smrities after 2nd century AD, though the period of mass untouchability is given as 18th and 19th century AD, which came as a result of several famines and consequent extreme poverty. The treatment of the book is on modern scientific lines dipped in spirituality, as preached by Swami Vivekananda. While highlighting the plight of Dalits in the past and present period, the author has not lost sight of whatever is good and grand in Hindu philosophy.
Keywords: Dalit